2011
DOI: 10.1371/journal.pone.0022639
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Lymph Node and Splenic Stroma in Mice with Induced Inflammatory Melanomas Is Associated with Impaired Recruitment of T and Dendritic Cells

Abstract: Migration of dendritic cells (DC) from the tumor environment to the T cell cortex in tumor-draining lymph nodes (TDLN) is essential for priming naïve T lymphocytes (TL) to tumor antigen (Ag). We used a mouse model of induced melanoma in which similar oncogenic events generate two phenotypically distinct melanomas to study the influence of tumor-associated inflammation on secondary lymphoid organ (SLO) organization. One tumor promotes inflammatory cytokines, leading to mobilization of immature myeloid cells (iM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Restoration of the LN structure is necessary for regaining immunocompetence (66). Chronic inflammation in tumor-draining LNs results in a disruption of the stromal network and loss of T-cell-zone FRCs, leading to a decrease in CCL21 and a reduced T cell influx to the LNs (67). Our work demonstrated that LN remodeling also occurred acutely following tolerance induction.…”
Section: Days) Data Presented As Mean ± Sem (A-d) or Percent Survivamentioning
confidence: 61%
“…Restoration of the LN structure is necessary for regaining immunocompetence (66). Chronic inflammation in tumor-draining LNs results in a disruption of the stromal network and loss of T-cell-zone FRCs, leading to a decrease in CCL21 and a reduced T cell influx to the LNs (67). Our work demonstrated that LN remodeling also occurred acutely following tolerance induction.…”
Section: Days) Data Presented As Mean ± Sem (A-d) or Percent Survivamentioning
confidence: 61%
“…[24] This immunosuppression occurs even in the absence of sentinel-node involvement[25], suggesting that it may be partly mediated by the release of different cytokines from the primary tumor. [2629]…”
Section: Discussionmentioning
confidence: 99%
“…This network is, in part, comprised of the stromal fiber ER-TR7 secreted by FRC (19) and the disruption of this network results in insufficient or improper immune responses to immune challenge (12, 3032). FRC build, remodel, and maintain the fiber network that gives the LN shape, defines microdomains within the LN, and provides a platform and directional cues via cytokines and chemokines for lymphocyte migration (19, 33, 34).…”
Section: Discussionmentioning
confidence: 99%